Rejuvenation of Jhum Lands through Bio-terracing - Kumar, Rakesh; Krishna, Bal; Kumar, Manoj; Kumar, Sanjeev (Indian Horticulture, 2024)
In the hilly regions of Northeastern India, shifting cultivation, locally known as jhum or slash/burn agriculture, has been the predominant form of farming, relying on traditional knowledge. However, this practice has led to a significant decline in soil fertility, rendering it unsustainable, particularly with increasing population and subsequent rise in food demands. To address this issue, implementation of bioterracing with the use of green-manuring species serves as a restorative measure to sustain soil fertility for agricultural purposes. It is important to note that soils in jhum areas are not only depleted of nutrients but also lack sufficient moisture, necessitating comprehensive soil conservation and improvement strategies.